Analysis of Students' Learning Obstacles on PISA-based Uncertainty and Data Content - Kusumayanti, Andi; Rahmi, Nurfadilah; Hairunnisa, Saskia; Amalya, Reski Putri; Fauzirah, Sri (Department of Mathematics Education, 2023)
Mathematical literacy ability is an ability that can be measured in PISA (Programme for International Student Assesment), one of the contents studied is uncertainty and data (Uncertainly and data). This study aims to describe the learning obstacles experienced by students in uncertainty material content and PISA-based data. This research is a type of descriptive research with a qualitative approach using didactical design (Didactical Design Research) didactic situation analysis stage before learning (prospective analysis). This research was conducted at SMP Pesantren Guppi Samata class VIII with a sample of 16 students using a test instrument in the form of 5 points of description questions and non-tests in the form of observation guidelines. Mathematical literacy indicators used in this study are Communication, Mathematising, Representation, Reasoning and argument, Devising strategies for solving problems, Using symbolic, formal , technical language and operations (Using symbolic, formal, technical and operating language), and Using mathematical tools. The results of this study include: 1) difficulties in understanding the problem; 2) Difficulty in formulating problems; 3) Difficulty in understanding the meaning of the problem; and 4) Difficulty in drawing conclusions. So that the obstacles faced by students are ontogenic obstacles and epistemological obstacles.